2014
DOI: 10.5901/jesr.2014.v4n6p19
|View full text |Cite
|
Sign up to set email alerts
|

Students' Readiness towards M-Learning: A Case Study of Pre-Service Teachers in Palestine

Abstract: This study examines pre-service teachers' (PST) attitudes towards, readiness to use and the nature of usage of mobile technologies. The main objective of the study is to explore the different aspects of M-devices in terms of the actual use, attitudes of use and willingness to use in learning context of PST in College of Education and Teacher Preparation (CETP) at An Najah National University (NNU) in Palestine. The results of the study could inform NNU administrators and faculty members about the possibilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…Nowadays, mobile devices are one of the leading innovative technological tools of communications and are considered a part of the lives of the young generation including students (Shaqour, 2014). The advent of these devices is accelerating and enhancing the trends of integrating such devices in education which provide flexibility in the overall education system.…”
Section: Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, mobile devices are one of the leading innovative technological tools of communications and are considered a part of the lives of the young generation including students (Shaqour, 2014). The advent of these devices is accelerating and enhancing the trends of integrating such devices in education which provide flexibility in the overall education system.…”
Section: Related Studiesmentioning
confidence: 99%
“…In addition, these factors also affect students' satisfaction of the technical aspects. Some researchers indicated that quality technical aspect of mobile learning affects students' satisfaction and use of mobile learning (Affouneh et al, 2020;Ibrahim et al, 2016;Shaqour, 2014).…”
Section: Related Studiesmentioning
confidence: 99%
“…Moreover, the number of sales is growing each day. Mobile devices are one of the leading innovative technological tools of communication which can be considered part of the lives of the young generation including students (Shaqour 2014). The development of mobile technology has been attracting children's attention to 3 (page number not for citation purpose) meaningful whole' (p. 6).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, according to the recent strategic plan (2017-2022), the Ministry of Education and Higher Education in Palestine moves towards -digitalizing education to make milestone change in the educational process‖ 1 . There were several attempts to propose different mobile based solutions and investigating students' readiness to use m-learning [25], [26]. For instance, the work reported in [25] investigated the teachers' willingness to and attitudes towards the use of m-learning applications in a higher education institution.…”
mentioning
confidence: 99%
“…Also, lack of resources and applications for content, limited connectivity and unreliable Internet connection with Wi-Fi and 3G/4G networks in Palestine were also mentioned by the participants. Another study [26] shows a high percent of students who are aware of mobile learning and are willing to use it in their courses. However, the previous mentioned studies are conducted in the context of higher education institution rather than elementary schools.…”
mentioning
confidence: 99%